Fogyasztásföldrajzi dimenziók a posztszocialista térségben - Szabó Pál („RIK-U” Kft., 2020)
A Kelet- és Kelet-Közép-Európában lezajlott rendszerváltozás utáni időszak területi társadalmi, gazdasági folyamatai több szempontból eltértek a kontinens többi térségének jegyeitől. Ez vonatkozik a napjaink egyik kiemelt jelenségére, a fogyasztásra is. E tanulmányban arra teszünk kísérletet, hogy felvillantsuk, hogy az aktuális fogyasztásföldrajzi dimenziókban milyen jellegzetességei vannak a posztszocialista térségnek, különös tekintettel az élelmiszerfogyasztásra és kiskereskedelemre.

Abstract. In this study, we attempt to shed light on the characteristics of the post-socialist area in the current dimension of the geography of consumption, with particular reference to the food consumption and retail. The territorial issue of the phenomenon of consumption has become complex in the postsocialist region: on the one hand, despite the 30 years after the change of regime, there are still signs of their isolation, however, the resemblance to the southern peripheries is also present in some dimensions of consumption, on the other hand, while the post-socialist bloc is becoming more diverse in terms of consumption, at the same time, however, global phenomena and technological advances reinforce the standardization of consumption and conditions.
Dimensions of the geography of consumption in the post-socialist area
https://kmf.uz.ua/wp-content/uploads/2020/09/final_1_kotet-foldrajzfkonf-2020-07-14.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00008119
Keywords: fogyasztásföldrajz; posztszocialista térség; élelmiszerfogyasztás; kiskereskedelem